Hybrid Buildings - Steven Holl (Oz, 2014)
In the 21st century, what is the potential of Hybrid Buildings? Certainly the hyper-urbanization of cities in China, such as Shenzhen, Beijing and Chengdu, can act as catalyst incubators for new and experimental architectural types.